Development Of Student Worksheets Based On Hots And Realworld Problems On The Topic Of Graphs - Andhany, Ella (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
This study aims to develop student worksheets based on Higher Order Thinking Skills and real-world problems on graph topics. The type of research used is development research to produce valid and practical products in the form of HOTS-Based Student Worksheets and real-world problems. The development model used is the 4D model (define, design, develop, dissemination) by Thiagarajan. The research subjects were 40 Mathematics Education students of UIN North Sumatra, semester VII of the 2024/2025 academic year, the object of the research was the graph topic in the Advanced Discrete Mathematics course. The product quality test from Nieveen is the Validity Test and Practicality Test. The resulting product is a HOTS-Based Student Worksheet and real-world problems on graph topics consisting of 9 essay questions, with details of 4 questions for the cognitive analysis level, 2 questions for the evaluation level, and 3 questions for the creation level. The development product is declared very valid and very practical, so it can be used in Discrete Mathematics lectures on graph topics.